Recent Advances in Laser Utilization in the Chemical Modification of Graphene Oxide and Its Applications - Trusovas, Romualdas; Račiukaitis, Gediminas; Niaura, Gediminas; Barkauskas, Jurgis; Valušis, Gintaras; Pauliukaite, Rasa (Advanced optical materials, 2016)
A dramatic rise in research interest in laser‐induced graphene oxide (GO) reduction and modification requires an overview of the most recent works on this subject. Typical methods for the recognition and confirmation of modified graphene and its derivatives, such as Raman, Fourier‐transform infra‐red (FTIR), X‐ray photoelectron (XP), and ultraviolet‐visible (UV–vis) spectroscopies, are introduced briefly in this review. A major part of the survey is devoted to the main modification ways and the laser parameters used in the literature. A discussion of possible reduction and modification mechanisms is also presented. Recent applications, especially in the biomedical field such as cell therapy treatment, as well as significant results of GO modification, are discussed in detail. Finally, perspectives for the application of laser‐induced GO modifications in passive THz photonics and biomedicine are briefly addressed. Laser‐induced graphene oxide reduction: Lasers are often used for the effective and well‐controlled reduction of graphene oxide. Chemical graphene modification is easily performed online with laser‐induced graphene oxide reduction, changing the ambient conditions by adding required chemical compounds. Such photoreduced and modified graphene has a broad variety of applications in various fields from devices to sensors and medicine.